D2-40, a novel lymphatic endothelial marker: identification of lymphovascular invasion and relationship with axillary metastases in breast cancer D2-40, um novo marcador endotelial linfático: identificação de invasão linfática e relação com metástases axilares em câncer de mama - Vanessa Fortes Zschaber Marinho; Fernanda Squárcio Fernandes Sanches; Gislene Fátima Silva Rocha; Konradin Metze; Helenice Gobbi (Sociedade Brasileira de Patologia Clínica, 2008)
BACKGROUND: Studies of lymphatic vessels were limited by the lack of specific markers. Recently, they have become possible due to the release of new D2-40 antibody, a selective marker for lymphatic endothelium. The aim of our study was to compare neoplastic invasion in lymphatic and blood vessels detected in hematoxylin and eosin (H&E) and immunohistochemistry-stained sections. METHODOLOGY: A total of 123 cases of invasive mammary carcinomas were studied and sorted out into three subgroups according to axillary staging (macrometastasis, micrometastasis and lymph node negative). Lymphatic vessel invasion (LVI) and blood vessel invasion (BVI) were initially evaluated in histological H&E and immunohistochemistry-stained sequential sections. Lymphatic and blood vessel invasions were assessed by immunohistochemistry, employing D2-40 and CD31 antibodies, respectively. LVI and BVI were related to size, type, histologic grade of primary tumors, and the presence of metastasis. RESULTS: LVI was detected through H&E staining procedure in 17/123 cases (13.8%), and through immunohistochemistry procedure in 35/123 cases (28.5%) (kappa = 0.433). BVI was detected through H&E in 5/123 cases (4.1%), and through immunohistochemistry in 19/123 cases (15.4%) (kappa = 0.198). LVI and BVI were positively related to higher histologic grade of primary tumors (p < 0.05). LVI was also positively related to the presence of macrometastasis. CONCLUSION: The detection of lymphatic and blood vessel invasions through immunohistochemistry employing D2-40 and CD31 was higher than the detection through H&E, and it was related to higher tumor grade and metastasis in axillary lymph nodes. INTRODUÇÃO: Estudos de vasos linfáticos eram limitados pela ausência de marcadores endoteliais linfáticos específicos. Recentemente, eles se tornaram possíveis após liberação comercial do novo anticorpo D2-40, marcador seletivo para endotélio linfático. O objetivo do nosso estudo foi comparar invasão neoplásica em vasos linfáticos e sanguíneos detectada em secções coradas pela hematoxilina e eosina (HE) e imuno-histoquímica (IIQ). MATERIAIS E MÉTODOS: Foram estudados 123 casos de carcinomas mamários invasores subdivididos em três subgrupos de acordo com o estadiamento axilar: macrometástases (Mac-Met), micrometástases (Mic-Met) e linfonodo negativo (LNN). Invasão de vasos linfáticos (IVL) e de vasos sangüíneos (IVS) foi inicialmente avaliada em secções histológicas coradas pela HE e através da IIQ realizada em cortes seqüenciais. A invasão de vasos linfáticos e sanguíneos foi avaliada pela imuno-histoquímica, empregando-se respectivamente os anticorpos D2-40, e CD31. IVL e IVS foram relacionadas com tamanho tumoral, tipo e grau histológico dos tumores primários e com a presença de metástases. RESULTADOS: IVL foi observada pela HE em 17/123 casos (13,8%) e pela IIQ em 35/123 casos (28,5%) (kappa = 0,433). IVS foi observada pela HE em 5/123 casos (4,1%) e pela IIQ em 19/123 casos (15,4%) (kappa = 0,198). IVL e IVS estavam positivamente relacionadas com maior grau histológico dos tumores primários (p < 0,05). IVL também estava positivamente relacionada com a presença de macrometástases. CONCLUSÃO: A detecção IIQ, respectivamente por D2-40 e CD31, de invasão de vasos linfáticos e sanguíneos foi maior que a detecção feita em cortes corados pela HE e relacionou-se com maior grau tumoral e metástases em linfonodos axilares.